A review of the Forensic Entomology literature in the south‐eastern United States. Issue 5 (12th August 2021) - Byrd, Jason; Sutton, Lerah
Abstract: A comprehensive review of forensic entomology literature specifically relevant to the south‐eastern United States (Alabama, Arkansas, Florida, Georgia, Kentucky, Louisiana, Mississippi, North Carolina, South Carolina, Tennessee, the US Virgin Islands, and Puerto Rico) revealed a significant deficit in the availability of literature that may be applied to forensic casework or otherwise beneficial to the forensic entomology practitioner. While there are numerous articles relevant to this geographic region on topics including biodiversity, ecology, behavior, and anecdotal case studies, very little literature is available on the development and methods necessary to conduct case evaluations in forensic entomology. A dramatic scarcity of literature in this region specific to insect species commonly encountered in forensic entomology casework (i.e., Calliphora livida (Hall), Calliphora terraenovae (Macquart), Cynomya cadaverina (Robineau‐Desvoidy), Cynomya mortuorum (Linnaeus), Lucilia cluvia (Walker), Lucilia coeruleiviridis (Macquart), Lucilia cuprina (Weidemann), Lucilia eximia (Weidemann), Protophormia terraenovae (Robineau‐Desvoidy)) that would be utilized for casework was also identified. To remedy this deficiency, additional development and succession studies must be conducted and published that address the most common species of insects encountered in forensic casework in the south‐eastern United States. This article is categorized under: Forensic Biology > Forensic Entomology Abstract : The bronze bottle blow fly ( Lucilia cuprina ) (Weidemann) pictured above is common species in the south‐eastern United States. Despite its abundance, there is very little published literature on this and other common species that would be useful for forensic entomology casework.